Correlation of Differential Function and Glomerular Filtration Rate Estimated from Computed Tomography Based Renal Volume and Diuretic Renogram in Living Renal Donor - Rai, Bipendra DK; Gnyawali, Diwas; Poudyal, Sujeet; Pradhan, Manish; Chapagain, Suman; Luitel, Bhoj R; Chalise, Pawan R; Gyawali, Prem R; Sharma, Uttam K; Nepali, Rabin; Gurung, Ghanashyam (Journal of Institute of Medicine Nepal, 2022)
Introduction In renal transplant, creatinine and isotope studies are used for estimation of donor glomerular filtration rate (GFR). Studies have shown computed tomography measured renal volume can also be used. Our main objective was to assess the accuracy of volume based estimated GFR (vGFR) with DTPA in renal transplant. Methods An observational analytical study was conducted from July 2018 to June 2019 in Department of Urology and Kidney Transplant Surgery and Department of Radiodiagnosis in Tribhuvan University Teaching Hospital where a total of 38 eligible potential donors were evaluated and serum creatinine level, Computed tomography with contrast and DTPA renogram were used to measure GFR and differential function. Results The mean age of the donors were 42.8 ± 10.9 years with 70% of donors being females. Renal volume was not statistically different between male and female donors. There was moderate correlation between volume based and DTPA based GFR (r= 0.76) and differential function (r= 0.71). Compared to creatinine, volume based GFR estimate showed better correlation to DTPA renogram. There was no significant difference in differential function estimated by DTPA and volume based estimates (p = 0.96). The upper and lower limit of agreement between the volume based and DTPA based differential function was –4.7 and 4.6 respectively. Conclusion CT volume overestimates total GFR compared to isotope renogram but it has better correlation than creatinine based estimates. It can be used to estimate the differential function of the donor kidney.